Homologs of the yeast Tvp38 vesicle-associated protein are conserved in chloroplasts and cyanobacteria - Keller, Rebecca; Schneider, Dirk (Frontiers in Plant Science, 2013)
Vesicle transfer processes in eukaryotes depend on specific proteins, which mediate the selective packing of cargo molecules for subsequent release out of the cells after vesicle fusion to the plasma membrane. The protein Tvp38 is conserved in yeasts and higher eukaryotes and potentially involved in vesicle transfer processes at the Golgi membrane. Members of the so-called “SNARE-associated proteins of the Tvp38-family” have also been identified in prokaryotes and those belong to the DedA protein family. Tvp38/DedA proteins are also conserved in cyanobacteria and chloroplasts. While only a single member of this family appears to be present in chloroplasts, cyanobacterial genomes typically encode multiple homologous proteins. Mainly based on our understanding of the DedA-homologous proteins of Escherichia coli, it appears likely that the function of these proteins in chloroplast and cyanobacteria involves stabilizing and organizing the structure of internal membrane systems.